Computer vision systems : 10th International Conference, ICVS 2015, Copenhagen, Denmark, July 6-9, 2015, Proceedings /: 10th International Conference, ICVS 2015, Copenhagen, Denmark, July 6-9, 2015, Proceedings. (2015) - Unknown
No abstract available